Voltage stabilizer of the asynchronous low-frequency generator - Berzan V.P.; Tirshu M.; Postoronca S. (Problems of the Regional Energetics, 2008)
The new method of output voltage stabilization of the asynchronous generator with capacitor excitation is offered. Value of the basic magnetic stream of the three-phase generator is adjusted by consecutive connection of excitation winding outputs to a zero point. In result it is received more high-speed and exact system of stabilization of voltage in independence of the reason of a preset value deviation. Experimental check has confirmed efficiency of the offered way of asynchronous generator voltage stabilization and an opportunity of its use in independent wind power installations